CHARACTERISTIC FREQUENCY EXTRACTION FOR THE FAULT OF GEAR BROKEN TEETH BASED ON IHPS AND SPS - TAO JiuZhi; HUANG RunHua; MA WeiPing (Jixie qiangdu)
Regarding the vibration signal characteristics of gear with broken teeth,the fault characteristic frequency can be extracted by means of calculating IHPS（ Improved Harmonic Product Spectrum） and SPS（ Sideband Product Spectrum） after FFT when the vibration shock is not obvious. Verified by simulation analysis and experiment,the method is proved effective and can be a feasible path to early detection for such faults.